2010
DOI: 10.20473/ijtid.v1i1.3721
|View full text |Cite
|
Sign up to set email alerts
|

Intestinal Parasites Infection in AIDS Patients with Chronic Diarrhea at Dr. Soetomo General Hospital Surabaya

Abstract: One of the mayor health problems among HIV-infected patients is opportunistic infection due to the defect of immunity. A cross sectional study was showed current the prevalence of intestinal parasites infection in AIDS patients with chronic diarrhea were being treated at Dr. Soetomo General Hospital Surabaya during the period June 2007 to May 2008. Fecal samples were collected from 122 AIDS patients with chronic diarrhea. Samples were examined for intestinal parasites using modified acid fast stain. Ninety-sev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0
2

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 5 publications
0
3
0
2
Order By: Relevance
“…A study in Indonesia associated the occurrence of cryptosporidiosis (4.9% of 318 cases) in HIV-infected individuals with chronic diarrhea and CD4 T-cell counts < 50 cells/mm 3 [88]. A recent study in Indonesia indicated a very high percentage of cryptosporidiosis (52.5%) amongst 100 HIVinfected individuals presenting with diarrhea [89].…”
Section: Hiv-cryptosporidiosis In Asiamentioning
confidence: 99%
“…A study in Indonesia associated the occurrence of cryptosporidiosis (4.9% of 318 cases) in HIV-infected individuals with chronic diarrhea and CD4 T-cell counts < 50 cells/mm 3 [88]. A recent study in Indonesia indicated a very high percentage of cryptosporidiosis (52.5%) amongst 100 HIVinfected individuals presenting with diarrhea [89].…”
Section: Hiv-cryptosporidiosis In Asiamentioning
confidence: 99%
“…Poka et al (2012) reported that the presence of intestinal helminths is largely determined by the level of sanitation and environmental factors than the health conditions of individuals in a given population [8]. Intestinal parasitic infections, nonetheless, have been implicated in life-threatening diarrhoea among HIVpositive persons [9,10] resulting in loss of body weight, indigestion, anorexia and dehydration, [9,11].…”
Section: Introductionmentioning
confidence: 99%
“…The global burden for cryptosporidiosis was noted from several reports in Africa and Asia, 11.3% in Turkey [3], 6% in Iran [4], and the highest prevalence found in Uganda as much as 73.6% [5]. Indonesia data prevalence of the infection is available based on two studies ranging from 4.9-52.5% [6], [7]. Most studies revealed that the prevalence variation of Cryptosporidium sp .…”
Section: Introductionmentioning
confidence: 99%